Biofungicides for Improvement of Potato (Solanum tuberosum L) Production. (3rd October 2022) - Ehiobu, John; Idamokoro, Emrobowansan; Afolayan, Anthony
Abstract : Potato ( Solanum tuberosum L) cultivation originated from Peru in Latin America. The cultivation has spread fast across the globe due to its ability to cope in the warm tropical and temperate climate. It is spotted by the United Nations as the only tuberous crop that can compete with the cereals in productivity. Fungal disease infestation has been identified as a major challenge confronting the farmers during the cultivation and marketing processes. Farmers' reliance on Chemical fungicides has lost its credibility to the adoption of the use of biofungicides due to its toxic, high cost, and environmental hazard effects. The trend of the adoption of biofungicides by potato farmers is gaining ground at a fast rate. Various national governments are devising means of collaborating with the United Nations stakeholders through encouraging research funding and by organizing conferences that will enhance potato production. This could be achieved by minimizing losses through farmer's complete adoption of biofungicides. This review, therefore, examines the various botanicals with antimicrobial properties as potential biofungicide against fungi diseases of potato.